Osteoprotective effects of virgin coconut oil and ocotrienolrich fraction on biomechanical bone strength parameter / Dina Fariha Che Ab Ghani ... [et al.] - Che Ab Ghani, Dina Fariha; Uzaimi, A'isyah Nabila; Shuid, Ahmad Nazrun; Abdul Malik, Mohd Maaruf (2019)
The study aimed to determine the bone effect of combined therapy of virgin coconut oil (VCO) and palm oil tocotrienolrich fraction (TRF) on biomechanical bone strength parameters of the ovariectomised rat model fed with high fat diet and heated palm oil. Materials and Methods: Thirty-six right femora of female Sprague-Dawley rats were obtained from the previous study at Universiti Kebangsaan Malaysia (UKM). The bone samples were divided into six groups with six femora in each group: Shamoperated (SHAM), ovariectomised control (OVX), ovariectomised and given Premarin 64.5µg/kg (OVX+P), ovariectomised and given VCO 1.43ml/kg (OVX+V), ovariectomised and given TRF 30mg/kg (OVX+T) and ovariectomised and given combined therapy of VCO and TRF (OVX+VT); for 24 weeks of treatment. The right femora were wrapped completely in Phosphate Buffered Solution (PBS)-soaked gauze and aluminum foil and kept in the freezer (-80ºC). In the present study, the right femora were thawed at room temperature (25ºC) for two hours. The femora were analyzed for three-point bending test using Shimadzu, AG-X 500N machine controlled by proprietary software (Trapezium X Version 1.00, Shimadzu). Results: The data was tested for normality using the Kolmogorov-Smirnov test. The results showed that the data were normally distributed. The statistical tests used were the analysis of variance (ANOVA), followed by Tukey's HSD test. The Young modulus value of OVX+VT group was significantly higher than OVX+V and OVX+T groups (p<0.05). Conclusion: Combined supplementation of VCO and TRF have offered better bone protective effects than single supplementation with VCO or TRF in preventing bone loss of osteoporotic rat model.